2017
DOI: 10.3847/1538-4357/aa8f4a
|View full text |Cite
|
Sign up to set email alerts
|

Signature of a Newborn Black Hole from the Collapse of a Supra-massive Millisecond Magnetar

Abstract: The X-ray plateau followed by a steep decay ("internal plateau") has been observed in both long and short gamma-ray burst (GRBs), implying a millisecond magnetar operating in some GRBs. The sharp decay at the end of plateau, marking the abrupt cessation of the magnetar central engine, has been considered as the collapse of a supra-massive magnetar to a black hole (BH) when it spins down. If "internal plateau" is indeed the evidence of a magnetar central engine, a natural expectation is a signature from the new… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 76 publications
0
10
0
1
Order By: Relevance
“…For example, if we assumeṀ scales withṀ ∝ t −4/3 , the decay slope of the MAD luminosity would be different from 5/3, and the value of M fb would be an order of magnitude smaller than the results obtained in Section 3 (Kisaka, Ioka & Sakamoto 2017). Besides, we did not consider the BH evolution during the accretion and BZ processes, which can in principle affect the BH mass M • and spin parameter a • (e.g., Chen et al 2017;Lei et al 2017). However, for very low accretion rate as studied in this work, this effect might be ignored.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, if we assumeṀ scales withṀ ∝ t −4/3 , the decay slope of the MAD luminosity would be different from 5/3, and the value of M fb would be an order of magnitude smaller than the results obtained in Section 3 (Kisaka, Ioka & Sakamoto 2017). Besides, we did not consider the BH evolution during the accretion and BZ processes, which can in principle affect the BH mass M • and spin parameter a • (e.g., Chen et al 2017;Lei et al 2017). However, for very low accretion rate as studied in this work, this effect might be ignored.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Besides GRB 160821B, are there other short GRBs with an internal plateau showing these X-ray signatures? Recently, Chen et al (2017) found that the X-ray bump following the internal plateau of long GRB 070110 is a possible signature of a new-born BH from the collapse of a supra-massive magnetar and interpreted the X-ray bump as the result of a fall-back accretion onto the BH. Their work further encourages us to explore the possible X-ray signatures of the new-born BH in the case of NS-NS mergers, and to search for these signatures in the sample of short GRBs that show an internal plateau.…”
Section: Introductionmentioning
confidence: 99%
“…If our interpretation is correct, this may explain why some GRBs that present the internal plateau feature, still show late time central engine activity, manifested through flares and second shallow plateaus (Troja et al 2007;Perley et al 2009;Margutti et al 2011;Gao et al 2015Gao et al , 2017bZhao et al 2020). In the magnetar collapsing scenario, only flares or plateaus close to the internal plateau could be interpreted with fall-back accretion model (Chen et al 2017;Zhao et al 2020).…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Dai等人 [22] 在2006年提出新生中子星的磁重联过程可 以解释强烈的X射线耀发现象, 其间歇性和持续时标与 观测一致, 尤其对于解释短暴的X射线耀发有显著优 势. Lü等人 [23,24] 发现一些长暴和短暴的X射线平台后 伴随着陡降, 这表明磁星(或夸克星)在旋转变慢后会塌 缩为黑洞. Chen等人 [25] [30] 、额外的幂律谱成分 [31] 等. 其中额外的幂律谱 可从keV能段一直延伸到GeV, 然后可能出现截断 [32] .…”
Section: 在双中子星并合或塌缩星中 都可能产生一颗旋unclassified